Omega 3 Fatty Acid and Skin Diseases - Sawada, Yu; Saito-Sasaki, Natsuko; Nakamura, Motonobu (Frontiers in Immunology, 2021)
A human being is exposed to various external environmental factors. Especially, food intake is one of the most influential factors in daily lifestyle. Among nutrients taken from foods, ω3 polyunsaturated fatty acids (PUFAs) affects the various beneficial impact on inflammatory diseases. Furthermore, the metabolites from ω3 polyunsaturated fatty acids (PUFAs), such as resolvins, are known to have strong anti-inflammatory actions in allergic and inflammatory diseases. However, little is known about the actual impact of ω3 PUFAs metabolites on skin diseases. In this review, we focused on the summarized of these metabolites have strong anti-inflammatory actions in various inflammatory diseases or anti-tumor actions in malignancies, in addition to the actual effect of omega 3 PUFAs metabolites on various cells.